SR micro-XRF to study Pb diffusion using a one-dimensional geometric model in leaves of Brassica napus for phytoremediation. (February 2020) - Rubio, M.; Mera, M.F.; Cazón, S.; Rubio, M.E.; Pérez, C.A.
Abstract: The purpose of phytoremediation is the removal of contaminants by plants that grow in soils with high levels of specific contamination. The technological implementation of lead phytoremediation depends on the understanding of tolerance and growth phenomena of the plant in contaminated soil, uptake and translocation of this element and its accumulation in aerial foliage of the plant. This work provides results about diffusive transfer of lead across the xylem towards leaf blade (or lamina) of Brassica napus using a 1-dimension model that assumes Fick's Second Law. It uses mapping data of Pb concentrations measured by synchrotron radiation micro x-ray fluorescence in order to calculate the diffusion coefficient in soft tissue of leaves. The diffusion equation is solved for a flat leaf geometric model and the solution is fitted to experimental values of Pb concentrations of equivalent leaves, harvested from the same plant in progressive times of its growing cycle. The results of the diffusion coefficient were calculated in a zone (∼600 μm) outside the leaf xylem, where the Pb concentration profile determines a well-defined gradient. These results are original and provide a contribution to understand the dynamics of Pb retention in leaves. Highlights: SR micro-XRF for mapping of chemical elements in vegetable tissues. The diffusion equation can be used to assess the diffusion of lead in blade tissue of Brassica nappus leaves. Phytoextraction using Brassica napus plant to remove heavy metals from contaminated soils.